2004
DOI: 10.1061/(asce)0733-9364(2004)130:1(153)
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Success of a Construction Project

Abstract: Different researchers have tried to determine the factors for a successful project for a long time. Lists of variables have been abounded in the literature, however, no general agreement can be made. The aim of this paper is to develop a conceptual framework on critical success factors ͑CSFs͒. Seven major journals in the construction field are chosen to review the previous works on project success. Five major groups of independent variables, namely project-related factors, project procedures, project managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
404
0
18

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(434 citation statements)
references
References 20 publications
12
404
0
18
Order By: Relevance
“…Previous studies have identified many critical success factors (CSFs) for construction projects. Chan et al (2004) identified five groups of factors influencing the success of construction project implementation, namely project-related factors, project procedures, project management actions, human-related factors, and the external environment. Zwikael and Globerson (2006) explored the impact of 16 planning processes and identified the most sensitive processes for a successful project [37].…”
Section: Ppandc and Project Success In Phpmentioning
confidence: 99%
“…Previous studies have identified many critical success factors (CSFs) for construction projects. Chan et al (2004) identified five groups of factors influencing the success of construction project implementation, namely project-related factors, project procedures, project management actions, human-related factors, and the external environment. Zwikael and Globerson (2006) explored the impact of 16 planning processes and identified the most sensitive processes for a successful project [37].…”
Section: Ppandc and Project Success In Phpmentioning
confidence: 99%
“…Delay is one of the major risk factors for both contractors and owners and causes difficulties within the project and then leads to cost and time overrun. Chan (2004) highlighted that the cost overrun to be one of the most critical issue at the execution stage of the construction project. Also stated by (Van Der Westhuzien, 2005), the presence of cost overrun can be a reason behind the failure of a project.…”
Section: Factors Affecting Project Cost and Time Overrunmentioning
confidence: 99%
“…Project should perform functionality, management of the project and performance of the contractors during the process. In the other hand, Chan (2004) suggested that the key to a successful project completion and deliver is correct estimation, monitoring time performance, cost performance and the overall quality of the construction project.…”
Section: Factors Affecting Project Cost and Time Overrunmentioning
confidence: 99%
“…Work by Chan, Scott, & Chan, (2004) on construction projects identified that the use of project management procedures was one of five main groups of independent variables that may impact on project performance with the other four groups being: project-related factors, project management actions, human-related factors and the external environment. The adoption of processes and procedures can also be viewed through project organizational hierarchies, with related projects being part of larger programs of work, which in turn are part of portfolios.…”
Section: Literature Reviewmentioning
confidence: 99%